2010
DOI: 10.1016/j.ijgo.2010.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pregnant women and their newborns as seen at a tertiary‐care center in Karachi, Pakistan

Abstract: Vitamin D deficiency is high among pregnant urban Pakistani women and their newborns. This public health problem needs urgent attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
1
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 20 publications
7
59
1
20
Order By: Relevance
“…Healthcare workers in academic and research centers commonly use radioimmunoassays to evaluate vitamin D levels in pregnant women and newborns [1,2]. At the Sant Parmanand Hospital-a private, tertiary care, multidisciplinary hospital in Delhi, India-an enzymelinked immunosorbent assay (ELISA) was used to measure vitamin D 3 levels among affluent (defined as the ability to afford hospital expenses) pregnant women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare workers in academic and research centers commonly use radioimmunoassays to evaluate vitamin D levels in pregnant women and newborns [1,2]. At the Sant Parmanand Hospital-a private, tertiary care, multidisciplinary hospital in Delhi, India-an enzymelinked immunosorbent assay (ELISA) was used to measure vitamin D 3 levels among affluent (defined as the ability to afford hospital expenses) pregnant women.…”
mentioning
confidence: 99%
“…Values of at least 75 nmol/L corresponded to normal levels of 25(OH)D 3 ; those less than 50 nmol/L corresponded to deficient levels; and those between 50 and 74 nmol/L corresponded to insufficient levels [1]. In 3 (15.0%) women, 25(OH)D 3 levels exceeded 75 nmol/L; in 2 (10.0%), they were between 50 and 74 nmol/L; and they were below 50 nmol/L in 15 (75.0%) ( (P = 0.82) in 25(OH)D 3 levels between paired maternal and umbilical cord blood samples.…”
mentioning
confidence: 99%
“…This suggests that for normal vitamin D concentrations to be maintained in fetal blood, the normal vitamin D concentration is higher during than before pregnancy. 12 In conclusion, there was a high prevalence of vitamin D deficiency in the south Indian pregnant women and their newborns. Vitamin D deficiency increased the risk of low birth weight neonate and it also had an effect on the length of the baby, head circumference and chest circumference.…”
Section: Discussionmentioning
confidence: 86%
“…[4][5][6][7] Studies have shown a high prevalence of vitamin D deficiency among Turkish women and their infants and among pregnant women and their newborns (as assessed from cord blood) in Greece and Iran. [8][9][10] An Australian study concluded that insufficient prenatal and postnatal levels of vitamin D were found to place breastfed infants at high risk for vitamin D deficiency and poor bone formation and a study from Pakistan reported widespread vitamin D deficiency among pregnant women and a correlation between maternal and cord blood levels of vitamin D. [11][12][13] People of Indian origin, especially pregnant women, are known to have a high prevalence of vitamin D deficiency. [14][15][16] The present study was conducted with women presenting in labour in a tertiary-care centre at Tamilnadu, India.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency is common all around the world and has a prevalence of 26-98% in pregnancy, bringing concerns about its consequences and need for supplementation [1][2][3][4] . As vitamin D receptor is expressed widely in nucleated cells, it does not only have a role in calcium and bone homeostasis but also in various organs and system functions.…”
Section: Introductionmentioning
confidence: 99%